2017
DOI: 10.1002/ajp.22677
|View full text |Cite
|
Sign up to set email alerts
|

High reproductive effort is associated with decreasing mortality late in life in captive ruffed lemurs

Abstract: Evolutionary theories of senescence predict that a high allocation to reproduction during early life should have long-term deleterious consequences on future reproduction or survival because individuals have to face an energy allocation trade-off between reproductive effort and the maintenance of body condition. Using a high-quality dataset from 1,721 red ruffed lemurs (RRL, Varecia rubra) and 3,637 black and white ruffed lemurs (BWRM, V. variegata) living in captivity, we tested the existence of a trade-off b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…Former studies on other captive populations of vertebrates reached the same conclusion: no evidence of survival cost of reproduction could be found (Kengeri et al, ; Ricklefs & Cadena, ; Tarin et al, ; Tidière et al, ). For instance, Tidière et al, failed to detect a negative impact of reproduction on survival using a sample of 5,358 ruffed lemurs kept in a zoo. However, all referred former studies (including Tidière et al, ) had little opportunity for properly controlling for variance in resource acquisition, either through time or between individuals.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Former studies on other captive populations of vertebrates reached the same conclusion: no evidence of survival cost of reproduction could be found (Kengeri et al, ; Ricklefs & Cadena, ; Tarin et al, ; Tidière et al, ). For instance, Tidière et al, failed to detect a negative impact of reproduction on survival using a sample of 5,358 ruffed lemurs kept in a zoo. However, all referred former studies (including Tidière et al, ) had little opportunity for properly controlling for variance in resource acquisition, either through time or between individuals.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, Tidière et al, failed to detect a negative impact of reproduction on survival using a sample of 5,358 ruffed lemurs kept in a zoo. However, all referred former studies (including Tidière et al, ) had little opportunity for properly controlling for variance in resource acquisition, either through time or between individuals. The present study does control for various confounding variables and suggests that the lack of CoR in former studies is actually a true lack of CoR and not a spurious conclusion due to hidden sources of heterogeneity that had not been properly accounted for in statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many advantages to measuring senescence in laboratory populations, but it is not clear to what degree laboratory findings fairly represent aging in natural populations. Comparative research involving invertebrate and mammal species has shown the importance of contrasting laboratory/zoo and wild aging rates, as the two can be extremely different (Bonduriansky and Brassil 2002;Carey et al 2008;Dukas 2008;Kawasaki et al 2008;Rodríguez-Muñoz et al 2010;Sherratt 2010;Tidière et al 2017). One likely contribution to these differences is that laboratory conditions are relatively benign and free from physiological stressors, such as the need to locate and defend a resource (Scott 1998).…”
Section: Disentangling Maternal Age Effects 000mentioning
confidence: 99%